Força dos músculos respiratórios em crianças e adolescentes com asma: similar à de indivíduos saudáveis? - Oliveira, Cilmery Marly Gabriel de [UNIFESP] (2012)
OBJECTIVE: To compare children/adolescents with mild or moderate asthma and healthy subjects in terms of respiratory muscle strength, correlating it with spirometric variables in the former group. METHODS: This was a cross-sectional study involving individuals 6-16 years of age and clinically diagnosed with mild/moderate asthma, together with a group of healthy, age- and gender-matched subjects. We determined spirometric values, as well as MIP and MEP, and we selected three reproducible measurements (variation < 10%). RESULTS: We evaluated 75 patients with asthma and 90 controls. The mean age was 10.0 ± 2.6 years. There were no statistically significant differences between the controls and the asthma group regarding MIP (-89.7 ± 26.7 cmH2O vs. -92.2 ± 26.3 cmH2O; p = 0.541) or MEP (79.2 ± 22.9 cmH2O vs. 86.4 ± 24.0 cmH2O; p = 0.256). The groups were subdivided by age (children and adolescents: 6-12 and 13-16 years of age, respectively). Within the asthma group, there was a significant difference between the child and adolescent subgroups in terms of MEP (74.1 ± 24.1 cmH2O vs. 92.1 ± 21.9 cmH2O; p < 0.001) but not MIP (p = 0.285). Within the control group, there were significant differences between the child and adolescent subgroups in terms of MIP (-79.1 ± 17.7 cmH2O vs. -100.9 ± 28.1 cmH2O; p < 0.001) and MEP (73.9 ± 18.7 cmH2O vs. 90.9 ± 28.1cmH2O; p < 0.001). In the asthma group, spirometric variables did not correlate with MIP or MEP. CONCLUSIONS: In our sample, asthma was found to have no significant effect on respiratory muscle strength.